Factors Related to Sufferer Behavior in Preventing Tuberculosis Transmission in the Family - Majid, Ruslan; Zainuddin, Asnia; Sabilu, Yusuf; Irma, Irma; Nurjannah, Nurjannah (Window of Health : Jurnal Kesehatan, 2023)
Tuberculosis is an infectious disease caused by Mycobacterium Tuberculosis; the method of transmission is through the air by sneezing, splashing phlegm, or coughing from Tuberculosis sufferers. Family members who live in the same house as Tuberculosis sufferers have a very high risk of being infected with Tuberculosis. This research aims to determine the relationship between knowledge, attitudes, family support, and health workers' role in Tuberculosis sufferers' behavior to prevent transmission to families in the Puuwatu City Health Center working area. Kendari 2021. This research is quantitative research with a cross-sectional study approach. The population in this study was 54 TB sufferers. The sampling technique used was a non-random sampling technique, namely total sampling. Primary data was collected using a pre-tested questionnaire. The data that has been collected is then processed using the Chi-Square test (α=0.05). From the results of statistical analysis, the relationship between the independent variable and the dependent variable was obtained for the variables knowledge (ρ-value= 0.004), family support (ρ-value= 0.033), role of health workers (ρ-value= 0.049) and attitude (ρ -value= 0.067). The variables of knowledge, family support, and the role of health workers are related to the behavior of Tuberculosis sufferers to prevent transmission to the family. In contrast, the attitude variables are not related to the behavior of tuberculosis sufferers in order to prevent transmission to the family.